Secure hidden keyword searchable encryption schemewith fine-grained and flexible access control - Yang YANG; Bo-gang LIN; Mao-de MA (Tongxin xuebao)
Existing searchable encryption schemes have difficulties in key management for multiple users and could not provide fine-grained access control mechanism. Aiming at solving these problems, a hidden keyword searchable encryp-tion scheme with fine-grained access control was proposed utilizing CP-ABE (ciphertext-policy attribute based encryp-tion) algorithm. Data owners allocate specific and flexible access policy on their data that is stored on a third-party data server. Only those users that has attributes satisfing the access policy are authorized to search encrypted data and decrypt returned results. Moreover, the suggested system has the function to add and revoke user. Security analysis shows that the scheme could not only prevent the leakage of private data but also hide the information of keywords. It deters a third-party storage provider from intercepting users' sensitive information when a search function is provided. The effi-ciency analysis shows that the efficiency of retrieval keeps no more than tens of microsecond and this scheme is suitable for large scale system.